Utilization of Value-based Management in the Strategic Management of German Automotive Industry. Issue 4 (August 2019) - Raj, Razaq; Beck, Valentin; Soliman, Alaa
Abstract: The purpose of this research article is to analyse the value-based management commitment of automotive enterprises and to examine the factors that explain the control parameters in automotive industry. There have been a few empirical studies published in the German's automotive sector, but most of the existing studies failed to provide evidence of utilization of value-based management in the strategic management in the automotive sector. The German automotive industry's development is closely related to global economic developments. Previous research work has considered control parameters of enterprises, but there is little evidence on the factors that explain which control parameters are used in automotive industry. A survey based on annual reports from 2008 to 2011 is used. In total, 20 annual reports of automotive companies were analysed. The results show that automotive companies, especially original equipment manufacturers and listed suppliers, have committed to value-oriented management and have implemented value-oriented approaches. However, not all of the suppliers are communicating this in their reports. The results also show that economic value added is the leading key indicator in the automotive industry.